2016
DOI: 10.1038/srep37201
|View full text |Cite|
|
Sign up to set email alerts
|

Intronless WNT10B-short variant underlies new recurrent allele-specific rearrangement in acute myeloid leukaemia

Abstract: Defects in the control of Wnt signaling have emerged as a recurrent mechanism involved in cancer pathogenesis and acute myeloid leukaemia (AML), including the hematopoietic regeneration-associated WNT10B in AC133bright leukaemia cells, although the existence of a specific mechanism remains unproven. We have obtained evidences for a recurrent rearrangement, which involved the WNT10B locus (WNT10BR) within intron 1 (IVS1) and flanked at the 5′ by non-human sequences whose origin remains to be elucidated; it also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…WNT10A rs10177996, investigated in the present study, was previously shown to have a marginal association with increased uptake of saturated fat in colorectal adenoma patients, which in turn was shown to induce cell proliferation increasing the risk of colorectal cancer . Furthermore, variation in WNT10B resulting in an intronless WNT10B ‐short variant was shown to underlie acute myeloid leukaemia . Interestingly, additional WNT pathway genes, for example DKK1 and KREMEN1 , have been recently implicated in the aetiology of familial tooth agenesis, broadening the spectrum of candidate genes for tooth agenesis in this pathway, while DKK1 has also been demonstrated to promote migration and invasion of non‐small cell lung cancer …”
Section: Discussionmentioning
confidence: 63%
“…WNT10A rs10177996, investigated in the present study, was previously shown to have a marginal association with increased uptake of saturated fat in colorectal adenoma patients, which in turn was shown to induce cell proliferation increasing the risk of colorectal cancer . Furthermore, variation in WNT10B resulting in an intronless WNT10B ‐short variant was shown to underlie acute myeloid leukaemia . Interestingly, additional WNT pathway genes, for example DKK1 and KREMEN1 , have been recently implicated in the aetiology of familial tooth agenesis, broadening the spectrum of candidate genes for tooth agenesis in this pathway, while DKK1 has also been demonstrated to promote migration and invasion of non‐small cell lung cancer …”
Section: Discussionmentioning
confidence: 63%
“…Recently, WNT10B/FZD4 interaction in the MCF7 breast cancer cell line suggests an autocrine activation of Wnt signalling in this cell line model (Lazzaroni F. et al, 2016). In melanoma FZD4 binds WNT5A and stimulates tumor invasion through activation of βcatenin signaling (Grossman A. et al, 2013), while in acute myeloid leukemia the interaction between WNT3A and FZD4 induce higher resistance against apoptosis (Tickenbrock L. et al, 2008).…”
Section: Functionmentioning
confidence: 96%
“…Visualization of FZD4/WNT10B interaction in MCF7 adherent (top) and tumorsphere (bottom) by proximity ligation assay (Lazzaroni et al,2016).…”
Section: Figurementioning
confidence: 99%
“…Therefore, Wnt/β-catenin signaling rapidly enhances RUNX1 expression in leukemia-derived cell lines and human CD34+ hematopoietic cells, suggesting that transcriptional deregulation of translocation-prone genes occurs prior to translocation [93]. Furthermore, recent results highlight the role of Wnt signaling in AML, describing a new rearrangement leading to WNT10B overexpression, with the exception of clinical contexts with recurrent cytogenetic abnormalities [94], suggesting a different mechanism promoting Wnt signaling activation in CBFL. In line with these findings, it appears interesting the functional relevance of Wnt signaling induced by CBFL fusion proteins via plakoglobin (γ-catenin) induction [95], which provides a possible explanation of the different molecular circuitry involved in Wnt signaling activation as a common feature of several balanced translocations in AML ( Figure 5).…”
Section: Epigenetic Silencing Of Mir-193a Contributes To T(8;21)-medimentioning
confidence: 99%